Susceptibility of Contact Lens-Related Pseudomonas aeruginosa Keratitis Isolates to Multipurpose Disinfecting Solutions, Disinfectants, and Antibiotics - Khan, Mahjabeen (Transl Vis Sci Technol, 2020)
PURPOSE: This study analyzed the susceptibilities of 17 contact lens (CL)-related keratitis isolates of Pseudomonas aeruginosa from Australia to antibiotics, multipurpose contact lens disinfecting solutions (MPDS), and disinfectants through minimum inhibitory (MIC) and minimum bactericidal concentrations. METHODS: Antibiotics included ciprofloxacin, levofloxacin, gentamicin, tobramycin, piperacillin, imipenem, ceftazidime, and polymyxin B. The MPDS OPTI-FREE PureMoist, Complete RevitaLens OcuTec, Biotrue, and Renu Advanced Formula and the constituent disinfectants; alexidine dihydrochloride, polyquaternium-1, polyaminopropyl biguanide, and myristamidopropyl dimethylamine (Aldox) were analyzed. The combined susceptibility of disinfectants based on the MPDS formulation was assessed through fractional inhibitory concentration. RESULTS: All isolates were susceptible to levofloxacin and gentamicin, 2/17 were resistant to ciprofloxacin; 1/17 was resistant to tobramycin, piperacillin, and polymyxin; and 3/17 were resistant to ceftazidime whereas 12/17 were resistant to imipenem. Of the four MPDSs, for Renu Advanced Formula 8/17 strains have an MIC ≤ 11.36 for OPTI-FREE PureMoist 14/17 strains have an MIC ≤ 11.36% for Complete RevitaLens 9/17 strains have an MIC ≤ 11.36, and for Biotrue 5/17 strains have MIC = 11.36. All strains were killed by 100% MPDS. At the concentrations used in the MPDSs, individual disinfectants were not active. From three tested isolates, no synergy was found in dual combinations of disinfectants. However, synergy was found for triple combination of disinfectants for three tested strains. CONCLUSIONS: Australian CL-related isolates of P aeruginosa were susceptible to most antibiotics. There was variability in susceptibility to different MPDS. Individual disinfectant excipients had limited activity. The combination of the disinfectants showed synergy, antagonism, and no interaction. TRANSLATIONAL RELEVANCE: This study will help to choose better preventive and treatment measures for microbial keratitis.